THE SHARING OF FLOOD WATERS IN THE KSOURS OF GHARDAIA AND BERRIANE (ALGERIA) HYDRAULIC STUDY - Khelifa, Ali; Remini, Boualem (GeoScience Engineering, 2019)
The present article deals with two systems of sharing flood waters used in the oases of Ghardaïa and Berriane. Based on bibliographic work, and data collection and investigations performed during the period between 2006 and 2018 near the Ksourian population as the floods are the only source of water for both oases. Ancestral hydraulic systems of sharing and regularizing floods were implemented in both oases. Each hydraulic system is composed of several hydraulic structures (e.g. dams, spillways, galleries, wells) that have been designed taking into considerations the geomorphology and topography of the region. This study compares the two systems and proves that although built 7 centuries ago, both the systems were built with intelligence. They have become parts of the national heritage and must be preserved for future generations. Keywords: Ghardaïa, Berriane, flood, sharing waters. http://doi.org/10.35180/gse-2019-0011